Pengaruh Edukasi DAGUSIBU terhadap Pengetahuan Kader Desa Dasan Borok - Oktresia, Erma Ewisa; Gemantari, Baiq Maylinda (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
The inadequate knowledge about drugs usage might be leading to emerging the unwanted effect of drugs. Ikatan Apoteker Indonesia, the committee of pharmacists in Indonesia, by their DAGUSIBU program make an attempt to overcome that problem. To increase the public knowledge, DAGUSIBU is implemented by educate public about four principal of drugs usage as how to get; how to use; how to store; and how to dispose the drugs. By establishing this program especially for the cadre of posyandu program, it is hoped the cadre might have impactful role to arising the public awareness and knowledge about drugs usage. This research is aimed to increase the knowledge of the cadre in Dasan Borok Vilage about drugs usage by DAGUSIBU program. This research was designed as quasi experimental using pretest-posttest analysis by questionnaire and education treatment as instrument research. There were 30 cadres take this program as participants. As the results, its was known that education treatment significantly enhance participants knowledge about drugs usage proven by pretest and postest analysis using marginal homogeneity test.